Case Report: Fluzoparib for multiple lines of chemotherapy refractory in metastatic cutaneous squamous cell carcinoma with BRCA2 pathogenic mutation - Sun, Xin; Chen, Wenjuan; Qu, Xiujuan; Chen, Ying (Frontiers in Pharmacology, 2022)
Background: Poly ADP-ribose polymerase inhibitors (PARPis) are widely used for patients with BRCA1/2 mutations. However, until now, there is no available evidence reported for the efficiency of PARPis in cutaneous squamous cell carcinoma (cSCC). Case Presentation: We presented a case of a 40-year-old man patient diagnosed with metastatic cSCC, relapsing after multiple lines of chemotherapy. Liquid biopsy detected a BRCA2 pathogenic germline mutation (c.3109C > T), indicating PARPis might be effective for this patient. The patient achieved tumor stability, and progression-free survival was five months without severe adverse effect after taking fluzoparib. Conclusion: This result confirmed that PARPis were effective for metastatic cSCC patients with germline BRCA2 pathogenic mutations, and provided a new treatment option for this group of patients.